Methyl jasmonate treatment alleviates chilling injury and improves antioxidant system of okra pod during cold storage. Issue 4 (1st February 2023) - Liu, Yunfen; Liu, Yu; Chen, Qiumei; Yin, Feilong; Song, Mubo; Cai, Wen; Shuai, Liang
Abstract: Okra pod is sensitive to low temperature, which results in chilling injury under improper low‐temperature storage. This study aimed to evaluate the effect of different concentrations of methyl jasmonate (MeJA) treatment on okra pod stored at 4 ± 1°C for 12 days and illuminate the mechanism of MeJA alleviating chilling injury. Compared to the control, MeJA treatments maintained lower relative electric conductivity (REC), chilling injury (CI) degree, and lignin content, as well as higher total soluble solids, total soluble sugar, pectin content, and chlorophyll content. The factor analysis was applied to comprehensively evaluate the effects of MeJA so that 1 μmol/L MeJA was screened as the optimum concentration to maintain the okra quality throughout the storage time. In contrast with control, MeJA not only accelerated the generation of antioxidant substances (phenolics and flavonoids) but also increased the superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), and peroxidase (POD) activity, inhibited malondialdehyde (MDA), hydrogen peroxide (H2 O2 ) content accumulation, and the polyphenol oxidase (PPO) activity. This work confirmed that MeJA could effectively alleviate chilling injury and maintain the quality during cold‐stored by regulating reactive oxygen species (ROS) metabolism. These results provide theoretical guidance for the application of MeJA in okra storage and preservation. Abstract : MeJA treatment has maintained the quality of okra during the cold storage period. The optimal concentration of MeJA was 1 μmol/L which was selected through a comprehensive analysis of quality indicators by factor analysis. MeJA treatment alleviates chilling injury of the okra pod through activating the antioxidant system.